Lexical and sublexical effects on visual word recognition in Greek: comparing human behavior to the dual route cascaded model. Issue 10 (26th November 2017) - Kapnoula, Efthymia C.; Protopapas, Athanassios; Saunders, Steven J.; Coltheart, Max
ABSTRACT: We evaluated the dual route cascaded (DRC) model of visual word recognition using Greek behavioural data on word and nonword naming and lexical decision, focusing on the effects of syllable and bigram frequency. DRC was modified to process polysyllabic Greek words and nonwords. The Greek DRC and native speakers of Greek were presented with the same sets of word and nonword stimuli, spanning a wide range on several psycholinguistic variables, and the sensitivity of the model to lexical and sublexical variables was compared to the effects of these factors on the behavioural data. DRC pronounced correctly all the stimuli and successfully simulated the effects of frequency in words, and of length and bigram frequency in nonwords. However, unlike native speakers of Greek, DRC failed to demonstrate sensitivity to word length and syllabic frequency. We discuss the significance of these findings in constraining models of visual word recognition.